Analyzing Vocal Fold Frequency Dynamics Using High-Speed 3D Laser Video Endoscopy - Patel, Rita R.; Döllinger, Michael; Jakubaß, Bernhard; Pinhack, Hanna; Katz, Ute; Semmler, Marion (Laryngoscope, 2024)
Objective: To examine changes in lateral and vertical vibratory motion along the anterior, middle, and posterior sections of the vocal folds, as a function of vocal frequency variations. Methods: Absolute measurements of vocal fold surface dynamics from high-speed videoendoscopy with custom laser endoscope were made on 23 vocally healthy adults during sustained /i:/ production at 10%, 20%, and 80% of pitch range. The 3D parameters of amplitude (mm), maximum velocity opening/closing (mm/s), and mean velocity opening/closing (mm/s) were computed for the lateral and vertical vibratory motion along the anterior, middle, and posterior sections of the vocal folds. Linear mixed model analysis was conducted to evaluate the differences in (a) vocal frequency levels (high vs. normal vs. low pitch), (b) axis level (vertical vs. lateral), (c) position level (anterior vs. middle vs. posterior), and (d) gender differences (male vs. female). Results: Overall, the superior surface vertical motion of the vocal fold is greater compared with the lateral motion, especially in males. Along the superior surface, the mean and maximum closing velocities are greater posteriorly for low pitch. The location (anterior, middle, and posterior) along the superior surface is relevant only for vocal fold closing rather than opening, as the dynamics are different along the various locations. Conclusions: The study highlights the significance of assessing the vertical motion of the superior surface of the vocal fold to understand the complex dynamics of voice production. Level of Evidence: NA Laryngoscope, 2024.
CRIS-Team Scopus Importer:2024-03-29
Keywords: high-speed videoendoscopy; laser endoscopy; three-dimensional imaging; vocal frequency